Knowledge of Parents toward Children with Attention Deficit Hyperactivity Disorder in Baghdad City (Indian Journal of Forensic Medicine & Toxicology, 2020)
Attention deficit/hyperactivity disorder (ADHD) is one of the most common psychiatric disorders in child andteenage psychiatry. ADHD children are at risk for a school organization constrains a multimodal treatmentdatabase1. This study surveys parent’s knowledge and attitudes towards attention deficit hyperactivitydisorder. The study aimed to assess the level of the knowledge and perspective for Parents who havechildren with Attention Deficit Hyperactive Disorder. A non-probability, purposive sample of 75 child and75 parents (40 mothers and 35 fathers), who had children with ADHD between the ages of (4 and 12) wereselected. A descriptive study was conducted at the Child Psychiatric Unit at Ibn Rushed Psychiatric TeachingHospital and Central Child Hospital Teaching in Baghdad City, from September8st to October 30th, 2017.A questionnaire format used for data collection and constructed by the researcher to achieve the objectivesof the study. Reliability of questionnaires was estimated through a pilot study which was carried out for theperiod from December 10th 2017 to December 30th 2017. Data were analyzed through the application ofdescriptive statistical analysis and the application of inferential statistic. The results of the study indicatethat the ADHD parents are no significant association between father knowledge and ‘ socio-demographicexcept income ,child age, gender and received medication which was correlated significantly at p-value 0.01respectively. The researcher recommended that future researches should be directed toward teaching parentsand teacher to increase their knowledge about the ADHD and provide many strategies to help them to reduceparents burden and coping .
Keywords: knowledge, Attention deficit hyperactivity disorder,Parents